Divertikulární choroba tračníku - zobrazovací metody - Sečkařová, D; Bočanová-Mlejnková, J; Votrubová, J (Rozhledy v chirurgii, 2013)
INTRODUCTION: Imaging methods are fundamental for diagnosis in patients suffering from diverticular disease of the large bowel. In case of complications, radiological intervention can be helpful for treatment. AIM: The authors aim to summarize current possibilities of imaging methods, both in diagnosis and treatment of diverticular disease. METHODS: Review of the literature and recent findings in the diagnosis of diverticular disease. CONCLUSION: The article presents the importance of imaging methods in the diagnosis and treatment of patients with diverticular disease.
Keywords: divertikl tlustého střeva; divertikulóza tlustého střeva; Diverticulum, Colon; Humans; Diagnostic Imaging; lidé; Diverticulosis, Colonic; diagnostické zobrazování